The Effect of Audit Quality, Good Corporate Governance and Deferred Tax Expenses on Profit Management in Manufacturing Companies 2019-2021 - Dwi Fitriyanto; Nur Annisa Miftahul Jannah (Tax Accounting Applied Journal, 2023)
These findings examine how deferred tax costs, audit quality, and The company's leadership procedure affects the profit managed in manufacturing companies in IDX during 2019 to 2021. Regression method Linear is needed as a quantitative approach as well as secondary data. By era 2019–2021, there were 51 business actors in the consumer goods industry sector. Retrieved 31 Companies are collected through a purposive sampling approach, which involves a number of criteria and determination of the state of the sample. Thus producing, The conclusion is audit quality, institutional ownership, and deferred tax costs has no impact on earning management. While the independent commissioner gave Impact on earning management.